Pendampingan Pelatihan Lagu Qur’any untuk Meningkatkan Kualitas Pembelajaran Al-Qur’an - Desy Naelasari; Khumairoh An-Nahdliyah; Nurul Lailiyah; Ali Mustofa; Nurul Indana (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2026)
This community service programme aims to improve the quality of Qur’anic learning through mentoring and training in the Lagu Qur'any programme at TPQ Al-Ikhlas, located in Nglele Village, Sumobito District, Jombang Regency. Lagu Qur-any is an innovative song-based learning medium whose lyrics are derived entirely from Qur’anic values and contain teachings related to faith (iman), worship (ibadah), and morality (akhlaq). This medium is designed to help students understand Qur’anic teachings in a more engaging, communicative, and memorable way. The programme employed a descriptive qualitative approach consisting of three stages: preparation, implementation, and evaluation. The participants were 30 TPQ students aged between 7 and 12 years. Data collection techniques included observation to identify changes in students’ participation and behaviour, semi-structured interviews with the TPQ management and teachers, and documentation as supporting evidence. Data were analysed qualitatively through data reduction, data display, and conclusion drawing. The results indicate a significant improvement in students’ ability to memorise Lagu Qur-any, increasing from 30% before the mentoring programme to 83.3% after its implementation. In addition, students demonstrated better understanding of faith, worship, and moral values, as well as increased confidence, enthusiasm, and active participation in Qur’anic learning activities. Therefore, the Lagu Qur-any mentoring programme has proven to be an effective and innovative learning model that enhances the quality of Qur’anic education in TPQ and supports the development of students’ religious character in a sustainable manner.